ABA-mediated transcriptional regulation in response to osmotic stress in plants - Fujita, Yasunari; Fujita, Miki; Shinozaki, Kazuo; Yamaguchi-Shinozaki, Kazuko (Journal of plant research, 2011)
The plant hormone abscisic acid (ABA) plays a pivotal role in a variety of developmental processes and adaptive stress responses to environmental stimuli in plants. Cellular dehydration during the seed maturation and vegetative growth stages induces an increase in endogenous ABA levels, which control many dehydration-responsive genes. In Arabidopsis plants, ABA regulates nearly 10% of the protein-coding genes, a much higher percentage than other plant hormones. Expression of the genes is mainly regulated by two different families of bZIP transcription factors (TFs), ABI5 in the seeds and AREB/ABFs in the vegetative stage, in an ABA-responsive-element (ABRE) dependent manner. The SnRK2-AREB/ABF pathway governs the majority of ABA-mediated ABRE-dependent gene expression in response to osmotic stress during the vegetative stage. In addition to osmotic stress, the circadian clock and light conditions also appear to participate in the regulation of ABA-mediated gene expression, likely conferring versatile tolerance and repressing growth under stress conditions. Moreover, various other TFs belonging to several classes, including AP2/ERF, MYB, NAC, and HD-ZF, have been reported to engage in ABA-mediated gene expression. This review mainly focuses on the transcriptional regulation of ABA-mediated gene expression in response to osmotic stress during the vegetative growth stage in Arabidopsis.